Filsafat Pendidikan Islam: Analisis Filosofis tentang Sistem dan Lembaga Pendidikan Islam - Munawar, Tri Huda; Hudda, Achyar (JOIES (Journal of Islamic Education Studies), 2017)
This article uses the content analysis model to analyze the Islamic education system. This paper aims to: (1) parse the meaning of the system, its characteristics and components, (2) find out the formulation model of the Islamic education system, and (3) know the form of Islamic educational institutions. The analysis concluded that; (1) system is a set of components or elements that interact with each other to achieve a goal, while the characteristics of the system in the form of components, ideas, concepts and principles that are integrated and interlocked. (2) the Islamic education system has its own model which is sourced from al-Qur'an and al-Hadith which are then excavated by ulama 'through ijtihad. (3) pesantren is an educational institution that is a component/sub-system of two education systems, namely the Islamic education system and the national education system